Cathedral at Durham
Following experience of castle assault during the Crusades, it was learned that a rectangular keep of the Norman sort was very vulnerable to undermining at the corners. The tendency in the intervening years was therefore toward polygonal towers, protected either by the motte of the older Norman castle, or by high surroundings walls or by both.